PENGARUH PENGETAHUAN PAJAK, PEMERIKSAAN PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK RESTORAN KABUPATEN TULUNGAGUNG - Putrinur'aini, Annisa; Pravitasari, Dyah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
Compliance with taxation is an important point that cannot be separated from the tax implementation process. In the implementation of taxation, tax obligations and rights to taxes must be fulfilled and implemented by every taxpayer, where must be carried out in accordance with existing standards and regulations. This study aims to see how big the effect of tax knowledge on restaurant taxpayer compliance, tax audit on restaurant taxpayer compliance, and tax sanctions on restaurant taxpayer compliance, especially in Tulungagung Regency. Quantitative methods are considered appropriate for this research, where the way to get data for research is through servers by relying on the distribution of questionnaires. The data obtained from the division of the questionnaire will then be processed again by multiple linear regression testing. The processed data obtained the results of restaurant taxpayer compliance in Tulungagung Regency is significantly and positively influenced by tax knowledge, restaurant taxpayer compliance in Tulungagung Regency is significantly and positively affected by tax audits, and restaurant taxpayer compliance in Tulungagung Regency is significantly and positively affected by tax sanctions.